Analyzing the Relationship between Corporate Entrepreneurship and Technology - Maestracci, Aria (Research Parks Publishing LLC, 2023)
A number of strategic and operational challenges have been presented to today's organizations as a result of environmental uncertainty, turbulence, and heterogeneity. It is becoming increasingly apparent that companies are turning to corporate entrepreneurship. This is in order to meet the challenge of simultaneously developing and nurturing both today's core competencies and those of tomorrow. In order to achieve this goal, this is what needs to be done. Consequently, it has become imperative that managers at all levels of the organization actively participate in the creation and implementation of a corporate entrepreneurship strategy in light of these facts. The literature has shown that successful corporate entrepreneurship (CE) is associated with improved firm performance, according to the general consensus, although not a total consensus, based on a number of studies that have been carried out in recent years. There are many ways in which corporate entrepreneurship can be viewed. However, it is becoming clearer and clearer as time goes on. This is because corporate entrepreneurship is an effective, valid, and feasible means of achieving high levels of performance at the organizational level. In addition to this, it is becoming increasingly recognized that executive coaching is one of the most effective and valid practices that can be applied to a wide range of firms and management levels in order to provide tangible and real advantages.